2017
DOI: 10.1158/0008-5472.can-15-3545
|View full text |Cite
|
Sign up to set email alerts
|

Bone Pain Induced by Multiple Myeloma Is Reduced by Targeting V-ATPase and ASIC3

Abstract: Multiple myeloma (MM) patients experience severe bone pain (MMBP) that is undertreated and poorly understood. In this study, we studied MMBP in an intratibial mouse xenograft model which employs JJN3 human MM cells. In this model, mice develop MMBP associated in bone with increased sprouting of calcitonin gene-related peptide-positive (CGRP+) sensory nerves and in dorsal root ganglia (DRG) with upregulation of phosphorylated ERK1/2 (pERK1/2) and pCREB, two molecular indicators of neuron excitation. We found th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 48 publications
4
90
0
3
Order By: Relevance
“…Our results are in agreement with previously published reports of bone marrow denervation in a mouse model of osteosarcoma; here, sarcoma‐inoculated mice also showed a decrease in limb use scores that were accompanied by multiple neurochemical changes in the cell bodies of the sensory neurons, potentially as a consequence of tumor‐induced bone marrow denervation. Interestingly, the only available report describing the sensory innervation of myeloma‐bearing femurs shows neuronal sprouting parallel to disease development, which has also been described in other models of cancer‐induced bone pain . Although it cannot be ruled out that myeloma‐inoculated mice also presented nerve sprouting prior to spinal compression and paraplegia development, our results suggest that pain‐related behaviors were present during the last 4 to 5 experimental days, suggesting that the denervation process had already been initiated in parallel to the development of pain‐related behavior.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results are in agreement with previously published reports of bone marrow denervation in a mouse model of osteosarcoma; here, sarcoma‐inoculated mice also showed a decrease in limb use scores that were accompanied by multiple neurochemical changes in the cell bodies of the sensory neurons, potentially as a consequence of tumor‐induced bone marrow denervation. Interestingly, the only available report describing the sensory innervation of myeloma‐bearing femurs shows neuronal sprouting parallel to disease development, which has also been described in other models of cancer‐induced bone pain . Although it cannot be ruled out that myeloma‐inoculated mice also presented nerve sprouting prior to spinal compression and paraplegia development, our results suggest that pain‐related behaviors were present during the last 4 to 5 experimental days, suggesting that the denervation process had already been initiated in parallel to the development of pain‐related behavior.…”
Section: Discussionsupporting
confidence: 77%
“…Although many preclinical models of MM are available, (36) currently only one study by Hiasa and colleagues (14) has addressed pain-related behaviors, but their results are mainly based on a xenograft myeloma model, which uses immunocompromised mice. However, mounting evidence has shown that the immune system plays a pivotal role in the transition from acute to chronic pain, (41,42) suggesting that the validity of xenograft models is compromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the control treatment, supplemented with NGF, did not produce a significant effect in the MFR, the DRG treated with secretome from resorbing osteoblasts (BS) presented a highly significative effect. Previous reports have shown that medium acidification and the molecules released by osteoclasts and matrix itself, upon matrix degradation, contribute to the activation of nociceptors on the nerve terminals (Hiasa et al, 2017; Yoneda et al, 2015a). Here we show that the secretome from mature, non-resorbing, osteoclasts, also contribute to the electrical activation and signal propagation across sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the structure-function of ASIC3 is of particular interest because there is substantial evidence supporting involvement of ASIC3 in pain (9,(23)(24)(25)(26)(27)(28), as well itch (29), mechanosensation (23,30) and anxiety (31). Although ASIC3 expression was initially thought to be restricted to the peripheral nervous system (and hence its original name, dorsal root ganglia acid-sensing ion channel, DRASIC (32)), we and others have demonstrated that ASIC3 is also expressed in both the spinal cord and numerous brain regions (33,34), which makes it even more important to understand how ASIC3 functions because any potential drug that targets ASIC3 for the treatment of pain may also produce side effects with the central nervous system.…”
Section: Introductionmentioning
confidence: 99%